Independent Control For Dual-PMSM Drives Using Five-Leg Inverter - Jurifa, Mat Lazi; Zulkifilie, Ibrahim; Marizan, Sulaiman; Azziddin, Mohamad Razali; Norazelina, Kamisman (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
This paper aims to implement an independent speed control for dual-PMSM drives fed by a single Five-Leg Inverter (FLI). In general, dual-motor drives are designed to reduce size and cost with respect to single motor drives. However, dual-motor drives using a single three-leg inverter has its limitation in the case of operation at different operating conditions and independent speed control requirement. By employing this FLI topology, the dual-motor drives can be used for four-quadrant control, variable speed operation and load disturbance rejection. In other words, it can be operated for different applications. This paper investigates the behaviour of independent speed control for Dual-Permanent Magnet Synchronous Motor drives. The speed and current controllers are implemented in d-q rotor reference frame using Simulink/MATLAB and the switching signals are generated by the built-in function and dSPACE. The overall performance of the drives is presented in terms of speed responses under forward and reverse operation. The three-phase current and quadrature current responses are also included. The experimental results of the drives under investigated study have proven that dual-PMSM can independently controlled by using FLI.